MARKETING STRATEGY ANALYSIS OF MICRO, SMALL, MEDIUM ENTERPRISE (CASE STUDY: FURNITURE INDUSTRY IN TOULIANG OKI VILLAGE) - Sualang, Maria Christy; Massie, James D.D; Pandowo, Merinda . (Universitas Sam Ratulangi, 2017)
Abstract: Small and Medium Enterprises are the backbone ofÂ major economy and empirical studies prove that small firms are more efficient and innovative in their operation, product development and marketing strategies. The objective in this study is to analyze marketing strategies of SMEâ€™s running entrepreneurs in Touliang Oki village. This study is qualitative studied about Marketing Strategy of Small and Medium Size Enterprises. A field survey method was faced to faced interviews were recorded to analyze the marketing strategies of Micro Sall Medium Enterprise Touliang Oki is one of the village in Minahasa, North Sulawesi. Most of them produce Furniture froom wood. Marketing strategy that they use is door to door and online shopping (facebook and whatsapp) strategy. Their innovations were in the shape of unique designs that not only meet the need of customers. Their services are innovative in a sense that they satisfy the customers. They also faced barriers like lack of raw material in this case they are used wood for the raw material and also they are still use standard machine makes their production is not maximal. Findings suggest to build initiatives some programs for students and lecturers to become business consultant of SME in Indonesia.Keywords: marketing strategy, micro, small, medium enterprise